The Vegetative State and the Science of Consciousness - Shea, Nicholas; Bayne, Tim (The British journal for the philosophy of science, 2010)
Consciousness in experimental subjects is typically inferred from reports and other forms of voluntary behaviour. A wealth of everyday experience confirms that healthy subjects do not ordinarily behave in these ways unless they are conscious. Investigation of consciousness in vegetative state patients has been based on the search for neural evidence that such broad functional capacities are preserved in some vegetative state patients. We call this the standard approach. To date, the results of the standard approach have suggested that some vegetative state patients might indeed be conscious, although they fall short of being demonstrative. The fact that some vegetative state patients show evidence of consciousness according to the standard approach is remarkable, for the standard approach to consciousness is rather conservative, and leaves open the pressing question of how to ascertain whether patients who fail such tests are conscious or not. We argue for a cluster-based 'natural kind' methodology that is adequate to that task, both as a replacement for the approach that currently informs research into the presence or absence of consciousness in vegetative state patients and as a methodology for the science of consciousness more generally.